Protein synthesis in the rumen from single or mixed sources of nitrogen - Richardson, D.; Akram, M. (Kansas Agricultural Experiment Station, 2011)
Opinion differs on the value of single or mixed sources of added protein in beef rations. This experiment was to determine the percentage total nitrogen and protein nitrogen present in rumen ingesta of steers fed a single source of nitrogen and combinations of two, three and four sources ( % nitrogen x 6.25-% protein). Four rumen-fistulated steers were used. Prairie hay served as the roughage; alfalfa hay, cottonseed oil meal, soybean oil meal and urea as sources of nitrogen. All feed ingredients were analyzed and equal amounts of added nitrogen were used in all cases. When mixed sources were used, each ingredient contributed an equal amount of nitrogen. Thus the rations fed were isonitrogenuos. Where urea was fed, corn was added to make the rations isocaloric. The first test was conducted without grain (except 1 pound daily with urea). The second test was conducted with added grain. One steer died from “hardware disease” at the end of the first test. That left only three steers, so alfalfa hay was omitted in the second test.
Keywords: Beef; Protein; Nitrogen; Rumen